2023
DOI: 10.3390/pharmaceutics15051323
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Fe(III)/Fe(II)-MPNs in Biomedical Applications

Abstract: Metal–phenolic networks (MPNs) are a new type of nanomaterial self-assembled by metal ions and polyphenols that have been developed rapidly in recent decades. They have been widely investigated, in the biomedical field, for their environmental friendliness, high quality, good bio-adhesiveness, and bio-compatibility, playing a crucial role in tumor treatment. As the most common subclass of the MPNs family, Fe-based MPNs are most frequently used in chemodynamic therapy (CDT) and phototherapy (PTT), where they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…Polyphenols and metal ions readily dissociate at low pH, enabling the controlled release of a metal ion, with Fe being the most common metal. MPNs have great potential in chemotherapy, as they can produce highly toxic hydroxyl radicals (•OH) that effectively help the drug kill tumor cells [ 123 ].…”
Section: Other Hybrid Networkmentioning
confidence: 99%
“…Polyphenols and metal ions readily dissociate at low pH, enabling the controlled release of a metal ion, with Fe being the most common metal. MPNs have great potential in chemotherapy, as they can produce highly toxic hydroxyl radicals (•OH) that effectively help the drug kill tumor cells [ 123 ].…”
Section: Other Hybrid Networkmentioning
confidence: 99%
“…9 As a new class of iron-based material, iron-based sulfides have attracted a lot of attention due to usage in biomedical applications, especially as nanomaterials. 10 Iron sulfide was shown to be more effective than ferrous ions at catalyzing the hydroxyl radical synthesis from hydrogen peroxide. [11][12][13] Moreover, the degraded nanoparticles have produced a relatively high concentration of exogenous H 2 S that causes mitochondrial and cellular cycle disruption of the cancer cells in the normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive research showed that iron-based metal-phenolic networks (MPNs) have great potential for drug delivery and cancer therapy [ 19 , 20 , 21 , 22 , 23 ]. The contained polyphenols provide interaction points for hydrogen and covalent bond formation, π–π stacking, hydrophobic interactions, and metal coordination [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%